Pengaruh Persepsi Kemudahan dan Persepsi Kegunaan Terhadap Keputusan Menggunakan Ovo Payment di Tunjungan Plaza Surabaya - Prety Indah Sari; Winarto (Journal Of Accounting and Business, 2022)
The purpose of this study was to analyze the effect of perceived convenience and perceived usefulness on the decision to use OVO Payment at Tunjungan Plaza Surabaya. The research population is Matahari Store consumers in Tunjungan Plaza Surabaya who transact using OVO payments. The sample consists of 100 OVO payment users at Matahari Store Tunjungan Plaza Surabaya. Data analysis was performed by multiple linear regression analysis. The results showed that perceived convenience has a significant influence on the decision to use OVO payment at Tunjungan Plaza Surabaya, perceived usefulness has a significant influence on the decision to use OVO payment at Tunjungan Plaza Surabaya, perceived convenience and perceived usefulness have a significant influence on the decision to use OVO payment at Tujungan Plaza Surabaya. Other results show that the perception variable is the dominant variable that influences the decision to use OVO payment.